Adaptação transcultural e propriedades de medida da Parkinson’s Disease Sleep Scale 2 (PDSS-2) - Pollyana Pereira de Oliveira (2023)
Introduction: Sleep disorders are a fairly common non-motor symptoms leading to functional limitations and poor quality of life in Parkinson's disease (PD). The gold standard diagnostic for diagnosing these illnesses is polysomnography, however it is expensive and not widely available. As thus, tools that evaluate these illnesses are crucial for both clinical practice and research. The Parkinson's Disease Sleep Scale (PDSS-2) replaces the original PDSS. This is the only specific tool to evaluate nocturnal sleep problems in people with PD. However, the instrument is not yet available in Brazilian Portuguese, and its transcultural adaptation and validation are necessary for use in the national scenario. Objective: This study aimed to cross-culturally adapt and test the measurement properties (reliability, construct validity, and interpretability) of the PDSS-2. Methods: In accordance with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) recommendations, this methodological study was conducted. The cross-cultural adaptation consisted of five stages: original translation, synthesis of translations, back translation, expert committee analysis, and testing of the pre-final version on 10 individuals with PD. In order to evaluate the measurement properties, the final version of the PDSS-2 Brazil was administered to 50 individuals with PD (66% men, mean age 75±11.9 years) twice (test and retest), distanced by a week. Internal consistency was measured using the Cronbach’s alpha coefficient. The test-retest reliability of individual and of the total score were evaluated using the squared weighted Kappa (Kw) and Intraclass Correlation Coefficient (ICC), respectively. The Bland-Altman plot analysis was adopted to estimate the precise limits of agreement with 95% confidence interval (CI) by calculating the standard error of measurement (SEM) and minimum detectable change (MDC). The severity of signs and symptoms of the PD (Movement Disorder Society-Parkinson's Disease Rating Scale, MDS-UPDRS), disease stage (Modified Hoehn and Yahr Scale, HY), sleep quality (Pittsburgh Sleep Quality Index, PSQI), excessive daytime sleepiness (Epworth Sleepiness Scale, ESS), depressive symptoms (Beck Depression Inventory, BDI), and perceived quality of life (Parkinson’s Disease Questionnaire, PDQ-39) were used to analyze the construct validity of the PDDS-2. Spearman's correlation coefficient was used to determine the magnitude and direction of the relationship between the PDDS-2 and these variables. Spearman’s correlation coefficient was used to determine the magnitude and direction of the relationship between the PDSS-2 and these variables. The occurrence of ceiling and floor effects, which are evident when more than 15% of the sample obtains the best result (zero) or the worst result (60 points), respectively, was used to examine interpretability. Results: The PDSS-2 Brazil showed a semantic, idiomatic, cultural and conceptual equivalence. The tested version demonstrated significant internal consistency with Cronbach's alpha of 0.64, adequate test-retest reliability for the individual items (Kw 0.59-0.98, 95% CI=0.30-0.95), and adequate test-retest reliability for the overall score (ICC=0.94; CI 95%=0.88-0.96), and no sign of ceiling or floor effects. The MDS-UPDRS (parts I, II, and III), PSQI, BDI, and PDQ-39 total scores were associated with the PDSS-2 total score. These findings guarantee the appropriate construct validity in accordance with the COSMIN criteria and support 88% of the generated hypotheses. Conclusion: The PDSS-2 Brazil is the only specific instrument in Brazilian Portuguese to measure sleep disorders in DP. It is a reliable tool that is valid for people with PD, easy to use, and inexpensive.